Quality Assessment of English Idiom Translation into Indonesian Among Primary School Students: A Pre-Test and Post-Test Study at SDN 101901 Lubuk Pakam - Risna Harvina; Desi Noviari; Muliawan Prayuda Putra; Nanda Kirana Silitonga; Abdollah Harahap; Dewi Nurmala (Jurnal Pendidikan Indonesia, 2026)
This study aims to assess the quality of English idiom translation into Indonesian among fifth-grade primary school students and to examine whether contextualized idiom instruction improves students' translation performance. The study employed a quantitative one-group pre-test and post-test design involving 20 fifth-grade students at SDN 101901 Lubuk Pakam. The instrument consisted of parallel translation tests containing English idiomatic expressions, and students' translations were assessed using a translation quality assessment framework covering accuracy, acceptability, and readability. The scores were analyzed using descriptive statistics, quality-category distribution, normality testing, and a paired-samples t-test. The findings revealed that students' mean score increased from 63.75 in the pre-test to 89.00 in the post-test, with an average gain of 25.25 points. The distribution of translation quality also improved substantially: before the intervention, most students were categorized as sufficient, poor, or good, whereas after the intervention all students reached either the good or very good category. The paired-samples t-test confirmed a statistically significant difference between pre-test and post-test scores, t(19) = 17.695, p < 0.001, with a very large effect size (Cohen's dz = 3.96). These results indicate that contextualized idiom instruction can significantly enhance primary school students' ability to translate English idioms into Indonesian accurately, naturally, and readably. The study suggests that idiom-based translation activities should be integrated into English learning at the primary school level to strengthen vocabulary mastery, figurative language awareness, and cross-cultural translation competence.